Experimental and numerical study of shear connection in composite beams of steel and steel-fibre reinforced concrete. (15th July 2020) - Zhang, Yujie; Liu, Airong; Chen, Bingcong; Zhang, Junping; Pi, Yong-Lin; Bradford, Mark A.
Highlights: The shearing capacity of high strength bolts in SFRC is higher than that in NC. The shear stiffness of high strength bolts in SFRC is higher than that in NC. Parametric studies on the shear behavior of high strength bolts were explored. Formulas were proposed to predict the shearing capacity of high strength bolts. Formulas were proposed to predict the load-slip curves of high strength bolts. Abstract: To explore the shear behaviour of high strength bolted connectors in steel-SFRC composite beams, push-out tests were carried out on 18 steel-fibre reinforced concrete (SFRC) specimens and 4 normal concrete (NC) specimens. The failure modes, ultimate shear strength, load-slip response as well as the shear stiffness of the tested specimens were determined accordingly. During the experiment, two failure modes that involved bolt shear failure and concrete splitting failure were observed in both NC and SFRC specimens. As the bolt-to-hole clearances of specimens were infilled, the slip plateau at the early loading stage therefor were avoided and the corresponding shear stiffness of bolted connectors increased as well. Compared to NC specimens, the extension of cracks on SFRC slabs were limited and the width of cracks efficiently decreased because of the addition of steel fibre in concrete. The ultimate shear strength of the bolted connectors in steel-SFRC composite beams was about 21.2% higher than that of the bolted connectors in steel-NC composite beams, with the volume percentage of steel fibre in concrete being approximate 1.0%. The applied pretension on bolted connectors had a significant effect on the shear stiffness of bolted connectors, but almost had no effect on the ultimate shear strength. The ultimate shear strength of bolted connectors increased with the increase of concrete compressive strength, bolt shank area and bolt tensile strength. Finite element models, which confirmed by the tested results, were also employed to perform the parametrical analysis involved in concrete compressive strength, as well as bolt pretension, and diameter and tensile strength. Upon the experimental and independent FE results, practical calculation formulas were further proposed, which can properly estimate the ultimate shear strength as well as the load-slip curves of high strength bolted connectors in steel-SFRC composite beams.